Strategi Pengendalian Efektif dalam Peningkatan Kualitas Layanan Pendidikan - Sunardi; Baihaki, Imam (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The main challenge facing educational institutions is to improve the quality of educational services through effective control. This article explores strategies that can be used by educational institutions to achieve excellence through effective control. The method used in this article is the study of literature used to explore and analyze various research, scientific articles, books, and other sources of information relevant to the topic of effective control in the context of educational institutions. The information obtained from these various sources is then analyzed to build a comprehensive understanding of strategies and best practices for effective control at educational institutes. The results of literary research show that effective controls can provide a variety of benefits to educational institutions. Among them are improved quality of education services, improved operational efficiency, better risk management, and improved institutional competitiveness in a global context. Some strategies that have proven effective in achieving effective control include the implementation of strong internal control systems, the use of information technology to enhance transparency and accountability, and the development of an organizational culture that supports responsibility and innovation.